2010
DOI: 10.1111/j.1365-2664.2010.01886.x
|View full text |Cite
|
Sign up to set email alerts
|

No place like home: an experimental comparison of reintroduction strategies using snakes

Abstract: Summary1. The practice of deliberately moving animals from one site to another for conservation is increasing as a tool to re-establish extirpated populations. Resource managers are faced with developing strategies for reintroduction attempts, but often lack experimentally derived evidence upon which to base decisions. 2. Using the northern water snake Nerodia sipedon sipedon in the USA, we compared the behaviour and performance of resident snakes with that of individuals translocated directly from the wild to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(109 citation statements)
references
References 56 publications
(104 reference statements)
8
98
3
Order By: Relevance
“…This movement pattern is similar to previous results (King et al 2004, Roe et al 2010. For example, captive-bred juveniles of the northern water snake (N. sipedon) showed low activity and used very limited areas during their early phase of release (Roe et al 2010).…”
Section: Movement Patterns Distances Moved and Home-range Sizesupporting
confidence: 90%
See 2 more Smart Citations
“…This movement pattern is similar to previous results (King et al 2004, Roe et al 2010. For example, captive-bred juveniles of the northern water snake (N. sipedon) showed low activity and used very limited areas during their early phase of release (Roe et al 2010).…”
Section: Movement Patterns Distances Moved and Home-range Sizesupporting
confidence: 90%
“…We only used the juveniles who successet al (2004) have studied the movement patterns, home ranges, uses of structural features, and hibernation mortality of captive-bred eastern massasauga (Sistrurus catenatus) in Wisconsin. Recently, Roe et al (2010) compared the movement and home range of captive-bred and wildcaught juveniles of the northern water snake (Nerodia sipedon). These studies have shown that rehabilitation projects combined with a successful captive breeding program might be applicable for the rehabilitation of endangered reptile species.…”
Section: Juveniles For the Study And Implanting Transmittersmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of enclosure effect on short-term movements might be interpreted as the enclosures lacking the appropriate stimulus for the development of familiarity, or preference, for the local habitat (Stamps & Swaisgood 2007, Roe et al 2010 or that the cage environment at Tallinn Zoo was sufficient. Alter natively, the facts that enclosure animals were more often found further from aquatic habitats, did not make longer daily movements, but appeared to cover slightly larger areas over time, suggest that enclosure animals may simply have been exploring more (and were perhaps better prepared for 'learning' about their new environment than were caged animals, see e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Biggins et al 1999, Stoin-ski & Beck 2004; see also Roe et al 2010), after which they may be released with or without further support in either a 'soft' release (with shelter and/or food) or a 'hard' release (with no support). The theoretical basis for this approach is that experience early in life (but not necessarily during any particular sensitive pe riod) affects future habitat preferences and individual performance, or behaviour, in that habitat (Davis & Stamps 2004, Stamps & Swaisgood 2007.…”
Section: Introductionmentioning
confidence: 99%